Do Religious Justifications Distort Policy Debates? Some Empirics on the Case for Public Reason. Issue 3 (September 2020) - Kettell, Steven; Djupe, Paul A.
Abstract: Scholars engaged in debates about the use of public reason often view religious arguments as being out of bounds. Yet the real-world impact of religious discourse remains under-explored. This study contributes to research in this area with an empirical test looking at the impact of religious arguments on a particular policy debate. A survey experiment explored the effects of religious and secular cues with varied policy directions on the issue of assisted dying. The findings showed that secular arguments were considerably more likely to elicit a positive response, and that, while religious arguments were not a conversation stopper, they produced significant distortions in political perceptions among participants, though not necessarily along the identity lines critical to the public reason debate.